Visual inspection on sources and factors of deterioration in wood components of Malay traditional house - Kamaruddin, Zumahiran; Nazuki, Siti Najwa (2015)
Wood is one of the principal materials for the construction of Malay traditional houses. However, the wood components are subject to deterioration due to the hot and humid tropical country like Malaysia. Therefore this study aims to investigate the sources and factors of deterioration on wood components of a traditional timber house, namely Rumah Dato’ Panglima Gajah in Negeri Sembilan. The house was selected as a case study due to its distinctive form and historical values. The main objectives of this study were to examine the types and properties of wood and to identify the sources and factors of wood deterioration in the house. Qualitative methods of data collection were employed including historical and site analyses, personal interview and site visit. Also, series of laboratory analyses were conducted in two different stages. The first stage of analysis was done to determine the type of wood, its properties and moisture content (MC). In the second stage, environment test was conducted to determine the Relative Humidity (RH) and surrounding temperature of the houses. Visual analysis was conducted on the wood components of the houses to identify and determine the types and factors of deterioration. The result shows that Meranti and Cengal woods were used for the house construction. The wood deteriorations are caused by environmental, biological and physical factors. The study found that Cengal has a minimal deterioration effect because of its higher density and higher resistance toward the environmental condition, termite attack and fungal infestation as compared to Meranti. The study suggests that environment surrounding of the house is the main factor of deterioration. Future research could be conducted to explore the suitable treatment for decayed wood. The Malay traditional houses need to be protected to ensure its heritage values are maintained in good condition.